River Notes: A Natural and Human History of the Colorado - La Point, Thomas W. (Ethnobiology Letters, 2013)
Review of River Notes: A Natural and Human History of the Colorado. Wade Davis. 2012. Island Press. Pp. 176 23.63 (Hardcover). ISBN 978‐1610913614.